Implementation of Merdeka Belajar-Kampus Merdeka in Pringsewu for Regional Tourism Resilience and Development: Penta Helix Collaborative Model and Actor-Network Theory Perspective - Yerik Afrianto Singgalen; A.Y. Agung Nugroho; Suharsono; Alfonso Harrison Nantingkaseh; Hironimus Cornelius Royke (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
: A collaborative approach between stakeholders can create regional tourism resilience from an institutional perspective. Therefore, stakeholders' level of interest and influence needs to be identified, classified, analyzed and evaluate comprehensively through case studies from the Penta Helix collaboration model and Actor-Network Theory (ANT) perspective. This study uses qualitative interpretative methods through a case study of the Merdeka Belajar Kampus Merdeka (MBKM) program conducted by the Atma Jaya Catholic University of Indonesia in research learning involving lecturers and students in Pringsewu Regency, Lampung. Data collection techniques using in-depth interviews, observations, and document studies. Meanwhile, a Focus Group Discussion (FGD) was also held involving the Tourism Awareness Group known as Kelompok Sadar Wisata (Pokdarwis), Tourism Destination Managers, and the Tourism Department of Local Government. The data processing of this research uses the triangulation technique to obtain valid and credible information. This study indicates that MBKM Project can integrate the stakeholders' interest and influence through various development programs to achieve tourism resilience which is beneficial for the socio-economic, socio-cultural, and socio-ecological dimensions. The Penta Helix collaboration model and ANT perspectives can monitor network development to identify key actors as senders, recipients, subjects, objects, assistants, and challengers in the actant scheme to optimize message translation for integrating interests.